Primate tarsal bones from Egerkingen, Switzerland, attributable to the middle Eocene adapiform Caenopithecus lemuroides - Erik R. Seiffert (PeerJ, 2015)
The middle Eocene species Caenopithecus lemuroides, known solely from the Egerkingen fissure fillings in Switzerland, was the first Paleogene fossil primate to be correctly identified as such (by Ludwig Rütimeyer in 1862), but has long been represented only by fragmentary mandibular and maxillary remains. More recent discoveries of adapiform fossils in other parts of the world have revealed Caenopithecus to be a biogeographic enigma, as it is potentially more closely related to Eocene adapiforms from Africa, Asia, and North America than it is to any known European forms. More anatomical evidence is needed, however, to provide robust tests of such phylogenetic hypotheses. Here we describe and analyze the first postcranial remains that can be attributed to C. lemuroides—an astragalus and three calcanei held in the collections of the Naturhistorisches Museum Basel that were likely recovered from Egerkingen over a century ago. Qualitative and multivariate morphometric analyses of these elements suggest that C. lemuroides was even more loris-like than European adapines such as Adapis and Leptadapis, and was not simply an adapine with an aberrant dentition. The astragalus of Caenopithecus is similar to that of younger Afradapis from the late Eocene of Egypt, and parsimony and Bayesian phylogenetic analyses that include the new tarsal data strongly support the placement of Afradapis and Caenopithecus as sister taxa to the exclusion of all other known adapiforms, thus implying that dispersal between Europe and Africa occurred during the middle Eocene. The new tarsal evidence, combined with previously known craniodental fossils, allows us to reconstruct C. lemuroides as having been an arboreal and highly folivorous 1.5–2.5 kg primate that likely moved slowly and deliberately with little or no capacity for acrobatic leaping, presumably maintaining consistent powerful grasps on branches in both above-branch and inverted postures.